Transferências intergovernamentais e seus impactos para a gestão da política pública de educação: análise sobre o caso do município do Rio de Janeiro, no período 2002/2011 - Souza, Elen Barreto Araujo de (2012)
This study seeks to identify the impact of intergovernmental transfers, given some of its specific features in the formulation and implementation of public education policy. Intergovernmental transfers are understood as an instrument adopted by federal states to correct intrinsic distortions of their mechanisms of collection and execution of certain powers by federal entities. Therefore, since it is the role of the State as provider of public goods and services to optimize their delivery, this paper seeks to understand how the mechanism of intergovernmental transfers adopted federal systems is reflected in the municipal budget, as well as in public policy decisions, analyzing specifically the case of education. For this, the case of the city of Rio de Janeiro is analyzed over the period from 2002 to 2011 as a reference for the study, since this is a city of relevance in the country and its experience may reflect the situation experienced by other cities, as well as serve as an inspiration for many others. This study has finally allowed us to understand that some policy choices are made as a result of funding mechanisms used by the States. It could be observed that although there is an understanding about the importance of having a national public policy project, there is a considerable gap between the perceptions of the central government and subnational entities on how best to provide a service, which hampers the optimal use of resources. Acknowledging this problem is paramount to improve the delivery of public services by the States.